2022
DOI: 10.3758/s13415-022-01037-5
|View full text |Cite
|
Sign up to set email alerts
|

Fear memory in humans is consolidated over time independently of sleep

Abstract: Fear memories can be altered after acquisition by processes, such as fear memory consolidation or fear extinction, even without further exposure to the fear-eliciting stimuli, but factors contributing to these processes are not well understood. Sleep is known to consolidate, strengthen, and change newly acquired declarative and procedural memories. However, evidence on the role of time and sleep in the consolidation of fear memories is inconclusive. We used highly sensitive electrophysiological measures to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…It has previously been reported that under certain conditions, aversive memories can strengthen over long retention intervals or during extinction (i.e., nonreinforced exposure to a CS) in both human and laboratory animals (Pavlov et al, 2023; Pickens et al, 2009; Poulos et al, 2016), and this learned fear “incubation” has been hypothesized to contribute to some posttraumatic stress responses (Careaga et al, 2016; Eysenck, 1968). Relatedly, “negativity bias” (in which an individual over-values negative outcomes relative to positive outcomes; Kahneman & Tversky, 1984) results from asymmetries in the activation in memory of positive and negative valence outcomes (Norris, 2021), and it has been observed that the representation of negative outcomes tend to be more stable and recede at a slower rate than positive outcomes (Norris et al, 2010).…”
mentioning
confidence: 99%
“…It has previously been reported that under certain conditions, aversive memories can strengthen over long retention intervals or during extinction (i.e., nonreinforced exposure to a CS) in both human and laboratory animals (Pavlov et al, 2023; Pickens et al, 2009; Poulos et al, 2016), and this learned fear “incubation” has been hypothesized to contribute to some posttraumatic stress responses (Careaga et al, 2016; Eysenck, 1968). Relatedly, “negativity bias” (in which an individual over-values negative outcomes relative to positive outcomes; Kahneman & Tversky, 1984) results from asymmetries in the activation in memory of positive and negative valence outcomes (Norris, 2021), and it has been observed that the representation of negative outcomes tend to be more stable and recede at a slower rate than positive outcomes (Norris et al, 2010).…”
mentioning
confidence: 99%